Building on firm competitive advantage through core competence manufacturing firm - Igho, Okpewho Lucky (International research journal of management, IT and social sciences, 2022)
The study examined the effect of core competence and firm competitive advantage in the Nigeria Brewing industry, with a focus on selected Brewing firms in Enugu, Onitsha and Benin City. The study employed a descriptive survey research design. Instrument adopted for the study is a structured questionnaire based on simple random sampling method. In addition, interview was also employed to serve as a compliment for the questionnaire. Reliability of the research instrument was tested using the Cronbach Alpha method which revealed that the instrument is reliable. The result of Durbin Watson revealed that the data is free from autocorrelation. Data analysis was done using both descriptive and inferential analysis technique. Descriptive statistics was used to give insight on the respondents profile while inferential statistics was used in the conducting of hypotheses. The two research questions for the study were analyzed using multiple regression model. The study shows that the two null hypotheses were rejected while the two alternative hypotheses were accepted (intellectual capital (p=0.000<0.05, ?=0.325) and customer services (p=0.000<0.05, ?=0.708).